2013
DOI: 10.1115/1.4022996
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative Heat Transfer Analysis of a Heat Pipe With Hybrid Axial Groove

Abstract: Through the application of thin film evaporation theory and the fundamental operating principles of heat pipes, a hybrid axial groove has been developed that can greatly enhance the performance characteristics of conventional heat pipes. This hybrid axial groove is composed of a V-shaped channel connected with a circular channel through a very narrow longitudinal slot. During the operation, the V-shaped channel can provide high capillary pressure to drive the fluid flow and still maintain a large evaporative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Our numerical and analytical solutions are compared to the ones of Wang and Schonberg and Wayner. It shows good agreement for moderate superheat temperatures; however, our analytical solution tends to underestimate total heat flux at large [5] o x x x Moosman and Homsy [15] o o x x Schonberg and Wayner [9] o o x x Stephan and Busse [7] o x x x Schonberg et al [16] o o x x Shikhmurzaev [17] x o x x Ma and Peterson [10] o x x x Pismen and Pomeau [18] x o x x Catton and Stroes [19] o o x x Choi et al [20] o x x o Qu and Ma [21] o o x x Choi et al [22] o x x o Park and Lee [23] o x x x By Morris [24] x o x x Demsky and Ma [25] o x x x Jiao et al [26] x o x x Na et al [27] o o x x Sultan et al [28] x o x x Wang et al [14] o x x x Ma et al [29] o x x x Wang et al [13] o o x x Zhao et al [30] o x x o Zhao et al [31] o x x o Benselama et al [32] x o x x Biswal et al [33] o x x o Liu et al [34] x o x x Bai et al [35] o o x x Biswal et al [36] o x x x Thokchom et al [37] o x x x Yang et al [38] o x x x Current study o o o o superheat temperatures. In addition, the model presented herein can be used to predict analytically and numerically all of the equilibrium film thickness, heat flux distribution, film thickness variation of evaporating film region, maximum total heat transfer rate through the evaporating film region, and ratio of the conduction to convection thermal resistance.…”
Section: Comparison Of Analytical Solution and Full Modelmentioning
confidence: 99%
“…Our numerical and analytical solutions are compared to the ones of Wang and Schonberg and Wayner. It shows good agreement for moderate superheat temperatures; however, our analytical solution tends to underestimate total heat flux at large [5] o x x x Moosman and Homsy [15] o o x x Schonberg and Wayner [9] o o x x Stephan and Busse [7] o x x x Schonberg et al [16] o o x x Shikhmurzaev [17] x o x x Ma and Peterson [10] o x x x Pismen and Pomeau [18] x o x x Catton and Stroes [19] o o x x Choi et al [20] o x x o Qu and Ma [21] o o x x Choi et al [22] o x x o Park and Lee [23] o x x x By Morris [24] x o x x Demsky and Ma [25] o x x x Jiao et al [26] x o x x Na et al [27] o o x x Sultan et al [28] x o x x Wang et al [14] o x x x Ma et al [29] o x x x Wang et al [13] o o x x Zhao et al [30] o x x o Zhao et al [31] o x x o Benselama et al [32] x o x x Biswal et al [33] o x x o Liu et al [34] x o x x Bai et al [35] o o x x Biswal et al [36] o x x x Thokchom et al [37] o x x x Yang et al [38] o x x x Current study o o o o superheat temperatures. In addition, the model presented herein can be used to predict analytically and numerically all of the equilibrium film thickness, heat flux distribution, film thickness variation of evaporating film region, maximum total heat transfer rate through the evaporating film region, and ratio of the conduction to convection thermal resistance.…”
Section: Comparison Of Analytical Solution and Full Modelmentioning
confidence: 99%
“…Pati et al [16] revealed that the electrostatic component of disjoining pressure can elongate the evaporating meniscus. Bai et al [17] developed a hybrid axial groove based on thin film evaporation theory and the fundamental operating principles of heat pipes. Guo et al [18] investigated effects of vertical mechanical vibration on evaporation heat transfer characteristics in rectangular microgrooves.…”
Section: Introductionmentioning
confidence: 99%
“…First, the present model associates the liquid average velocity directly with the liquid pressure gradient through the mass flow rate, and the third-order differential equation of the film thickness and first-order differential equation of the liquid average velocity are presented. Only first-order derivative of the liquid pressure with respect to x is need, [4,7,8,11,14,15,17]) for the first time. It is found that the total heat flux of the evaporating meniscus obtained by Model 3 is far lower than that obtained by Model 2.…”
Section: Introductionmentioning
confidence: 99%
“…Falling film dry out models and heat and mass transfer problems on various configurations and geometries have been studied by various researchers (Jiao et al [9], Mikielewicz et al [10], Volle et al [11], Grigore et al [12], Rahman et al [13], Fan et al [14], Bai. et al [15] and Kumar et al [16]).…”
Section: Introductionmentioning
confidence: 99%